Quality Improvement of Floor Cleaner Packaging Using Six Sigma and Continuous Improvement - Harira Setiawan, Ade; Nursanti, Ellysa; Indra Laksmana, Dimas (KnE Social Sciences, 2024)
There was a product defect in the 700 ML Lemongrass Refill Floor Cleaner packaging, which was 26,236 units from June to December 2021. The cost overrun was Rp. 15,085,700. This study aimed to improve the quality of the 700 ML Lemongrass Floor Cleaner packaging. The research method used was quantitative, and examined the quality of product packaging with Six Sigma and Continuous Improvement methods. The results of research conducted for the DPMO value before any improvement was 65,121 with a sigma level of 4.51. Then improvements were made so that the DPMO value became 12,517 with a sigma level of 5.26, resulting in a decrease in waste in the production process. So it can be concluded that we can provide solutions by replacing spare parts that are no longer suitable for use, making sure the machine is set correctly, making the standard materials used without defects and maintaining their shape, arranging the pouch arrangement as neatly and efficiently as possible, checking the pouch at the supplier, adjusting the machine settings, making sure it is neatly organized and performing regular machine maintenance according to the SOP. Keywords: continuous improvement, floor cleaner packaging, six sigma, quality